La paternidad obrera: Masculinidad, trabajo ferroviario y cuestión social en las revistas ilustradas de Argentina de principios del siglo xx - Palermo, Silvana Alejandra (2023)
This article examines representations of working-class fatherhood published in widely circulated magazines in Argentina at the beginning of the 20th century. It takes as a case study, the images of railroad workers, locomotive personnel-machinists and firemen-, in particular. In so doing, it seeks to highlight the relevance of commercial press in discussing both the modernity of the labour worlds in Argentina as well as the hardships of living and working conditions of the railroad workers and their families. In addition, this study pays attention to a less studied dimension of working-class masculinity: fatherhood. It explores the place of men in family life and seeks to shed light on prescriptive ideals regarding working-class fathers' responsibility and rights in modern Argentina.